CREATIVE LEADERSHIP OF RESORT BRAND: MENTAL AND PHYSICAL ACCESSIBILITY - Mendela , I.Ya.; О.І. (The actual problems of regional economy development, 2022)
Today, a strong creative brand is better than short-term sales surges, but few marketers are able to increase the mental and physical accessibility of the brand, let alone assess their effectiveness. There are very few marketing departments that are ready to grow invaluable market assets - the mental and physical accessibility of the brand. You need to segment, differentiate and have an idea of ​​the brand, but it is important for the brand manager to understand the competition between brands. Such managers will actively engage in branding, media strategies and distribution in order to improve marketing effectiveness. As marketers master the development and management of a brand's mental and physical accessibility, their importance to business will increase. This is a great opportunity for marketers, because no other part of the organization is responsible for measuring or managing these intangible assets – neither the product development department nor the customer service department. The main task of a marketer is to make the product easy to buy. To do this, it must be mentally and physically accessible to the client. Everything else is secondary, because the main competition between brands lies in the plane of accessibility. Mental accessibility requires expressive branding, while physical accessibility requires a dense network of distribution in time and space. Together, they make the brand creatively visible and create more opportunities to buy it. Creating a creative resort brand is not only the promotion of the resort business in order to make a quick profit, but also an important investment in the future of the resort. The concept of a resort brand consists of the main ideas of resort branding, which combine its goals and objectives, which becomes the basis for building a whole brand and marketing strategy. At the same time, the brand concept should contain all the feelings, ideas and goals of the resort. Resorts with a negative or insufficiently formed holistic image operate and have certain limitations or difficulties in the process of activity, so they cannot effectively achieve commercial success. Creating, developing and implementing a strategy of creative resort branding, the formation of the image of the resort require an integrated coherent policy, which does not have most resorts. The main stages of the brand formation process will contribute to the physical and mental accessibility of the resort brand. Key words:, , , , positioning, differentiation, loyalty.